Some notes on lithic materials from Tsaghkunk, a Neolithic-Chalcolithic site in the Ararat plain - Petrosyan, Artur (ARAMAZD: Armenian Journal of Near Eastern Studies, 2018)
A large area of the Ararat plain has been heavily deformed by modern agricultural activity, including the cultivation of land and the construction of a water channel. These activities have made prehistoric sites that originally bore non-pronounced landforms less visible in the current landscape. As a result of such heavy land deformations, reconstruction of the Ararat plain’s prehistoric landscape is becoming increasingly difficult. In this situation, it is worthwhile to gather fragmental information on prehistoric sites in the Ararat plain that were investigated during previous unpublished research, and then evaluate them through current scientific methods.